Meningkatkan Pengetahuan Masyarakat Mengenai Balai Pemasyarakatan - Fathoni, Muhammad Rizal; Faradila, Widya; Chomah, Isti; Pangestu, Marliyoda Aji; Gemilang, Mohamad Ridho Pijar; Arrisandy, Muhammad Zahniar (Yayasan Daarul Huda Kruengmane, 2024)
This community service program was carried out in Gilingan Village, Surakarta, Central Java, Indonesia. related to aspects of community social services and analysis of social reintegration policies which focus on the